Dampak Kebijakan Pelaksanaan Undang-Undang Nomor 28 Tahun 2009 Tentang Pajak Daerah dan Retribusi Daerah Terhadap Penerimaan PBBP2, Pajak Bumi dan Bangunan Perdesaan dan Perkotaan: (Studi pada DPPKAD Kabupaten Ciamis) (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research is motivated by initial observations that show that the Implementation of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies has not been optimal, as seen from the large number of tax arrears that must be fulfilled by the Ciamis Regency DPPKAD. PBBP2 (Rural and Urban Land and Building Tax) revenue has not reached the predetermined target. The increase in Regional Original Revenue (PAD) is carried out by following the right tax principles, including the application of sanctions for violations. This study uses a quantitative descriptive method with a population of 33 people, and a total sampling technique, so that the sample also totals 33 people. Data was collected using questionnaires. The results of the study show that the implementation policy of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies received a total score of 2262, which is included in the high category according to the benchmarks used. PBBP2 admissions at the Ciamis Regency DPPKAD received a total score of 2289, also in the high category. Based on hypothesis proof, the policy of implementing Law Number 28 of 2009 has an effect of 77.3% on the receipt of PBBP2 in the Ciamis Regency DPPKAD, while 22.7% is influenced by other factors that are not studied.